A STUDY ON EFFECT OF HUMAN RESOURCE MANAGEMENT PRACTICES AND EMPLOYEE JOB SATISFACTION IN PREDICTING ORGANIZATIONAL COMMITMENT IN HOSPITAL - Swati Tyagi; Dr. Nisha Agarwal (The Bioscan, 2025)
Objective The objective of this study was to identify the role of human resource management and employee job satisfaction in predicting organizational commitment in the healthcare sector. Research This study was done by quantitative survey research. In this study the independent variables are human resource management and employee job satisfaction and the dependent variable is organizational commitment. Results Human resource management is positively correlated with employee job satisfaction and organizational commitment. Both independent variables made significant contributions to the prediction of organizational commitment. Limitations As for the study convenient sampling is used hence the study have limited generalizability in other fields. This is cross-sectional study, there has to be caution in generalizing the results. Future Researchers may get more respondents from different geographical location. For thei study questionnaire was used to collect the data however it is recommended that future researchers should use other methods such as personal interview or telephonic interview to collect the data. Practical implications If there is a high level of job satisfaction among health care workers it will prevent low levels of turnover rate, absenteeism, levels of productivity and increase organizational commitment. HRM practices help in career development opportunities and better job opportunities. This study may suggest to ensure high levels of job satisfaction among employees and improved organizational commitment.